Current Results of Activities of Internal Affairs Preventive Inspectors in Uzbekistan - Temirova Mashkhura Muhammadaminovna (Genius Journals, 2022)
In this article, the actual results of the activities of preventive inspectors of internal affairs in Uzbekistan are analyzed on a scientific basis. Also, in the article, defining the main directions of the work of the base points of the Internal Affairs bodies and preventive inspectors operating in them, in order to effectively organize their activities, the scope of the main tasks of the base point and its subjects, and the regulations defining and regulating the implementation of these tasks - based on the analysis of legal documents, the activity of base points was divided into directions and its effect was analyzed with exact numbers.
Keywords: law; offense; prevention; reform